Persistent northward North Atlantic tropical cyclone track migration over the past five centuries - Baldini, Lisa M.; Baldini, James U. L.; McElwaine, Jim N.; Frappier, Amy Benoit; Asmerom, Yemane; Liu, Kam-biu; Prufer, Keith M.; Ridley, Harriet E.; Polyak, Victor; Kennett, Douglas J.; Macpherson, Colin G.; Aquino, Valorie V.; et al. (Scientific Reports, 2016)
Accurately predicting future tropical cyclone risk requires understanding the fundamental controls on tropical cyclone dynamics. Here we present an annually-resolved 450-year reconstruction of western Caribbean tropical cyclone activity developed using a new coupled carbon and oxygen isotope ratio technique in an exceptionally well-dated stalagmite from Belize. Western Caribbean tropical cyclone activity peaked at 1650 A.D., coincident with maximum Little Ice Age cooling, and decreased gradually until the end of the record in 1983. Considered with other reconstructions, the new record suggests that the mean track of Cape Verde tropical cyclones shifted gradually north-eastward from the western Caribbean toward the North American east coast over the last 450 years. Since ~1870 A.D., these shifts were largely driven by anthropogenic greenhouse gas and sulphate aerosol emissions. Our results strongly suggest that future emission scenarios will result in more frequent tropical cyclone impacts on the financial and population centres of the northeastern United States.